Paddy rice stored under hermetic conditions: the effect of relative humidity, temperature and storage time in suppressing Sitophilus zeamais and impact on rice quality - Carvalho, Maria Otilia (2018)
The aim of this study was to analyse the effect of relative humidity in suppressing Sitophilus zeamais, in paddy rice stored under hermetic conditions, during four and seven months, at different average temperatures, as well as the impact on rice quality. Hermetic bags, GrainPro® SuperGrainbag® Farm™, were used to store two rice varieties under three different relative humidities: 67%, 75% and 85% RH, and average temperatures of 14 C, 17 C and 24 C, both monitored by Hobo® Data loggers, with the probe placed inside the bags. CheckpointII Portable O2 and CO2 Gas Analyzer was used to assess gas contents on the top and bottom of each bag. At the end of the trials, paddy samples were collected to estimate water activity (aw). The rheology behaviour of rice pastes prepared with race flour obtained from the different treatments was also evaluated, using a controlled stress rheometer. The results showed that the response of the stored-product insects changes with environmental conditions, O2 and CO2 contents. Other parameters were considered; aw increased with relative humidity and temperature, but decreased with storage time. The relative humidity played an important role, together with the increase of temperature, in suppressing insect populations. A modified atmosphere was naturally produced inside the hermetic bag, under 85% RH, with low O2 and high CO2 contents, at different average temperatures, 14 C and 17 C. These results demonstrated that S. zeamais can survive, but has no progeny. Under the same conditions, but at the higher average temperature of 24 C, S. zeamais attained 100% mortality before producing progeny. The increase on respiration rate, registered by CO2 increase and O2 decrease, for higher RH values, reduced the viscoelastic functions and changed the starch gelatinization point of Indica and Japonica rice. The results obtained showed that storing paddy hermetically, at low relative humidity, did not change atmospheric content and maintained the viscoelastic functions of the rice pastes